A Comparative Study of Breast Sensibility and Patient Satisfaction After Breast Reconstruction: Autologous, 2-Stage Implant-Based, and Prepectoral Direct-to-Implant Reconstruction. Issue 3 (March 2022) - Hwang, Yong-Jae; Lee, Hyung-Chul; Park, Seung-Ha; Yoon, Eul-Sik
Abstract : Background: Currently, a variety of treatment modalities are implemented for breast reconstruction. However, clinical prognosis regarding sensory regeneration of the breast and patient-reported satisfaction remains underexamined. In this study, we aimed to compare breast sensibility after various reconstruction. Methods: We conducted a retrospective comparative study of all patients who underwent breast reconstruction between August 2016 and October 2019 at our institution. Acellular dermal matrixes were used to cover the implant inferolaterally in a dual-plane subpectoral approach and to wrap the implant in prepectoral direct to implant (DTI). The cutaneous tactile pressure threshold and patient satisfaction outcome were tested. Results: A total of 105 breasts were assessed, 30 breasts reconstructed with deep inferior epigastric perforator (DIEP) flap, 40 breasts reconstructed with 2-stage subpectoral implant, and 35 breasts reconstructed with prepectoral DTI. In the specific group-to-group analysis, DIEP and implant groups showed significant differences in sensory recovery, mainly in lateral areas of the reconstructed breast. In 2-stage reconstruction and DTI groups, there were no statistically significant differences. When comparing patient groups using only patients with follow-up lengths of more than 12 months, the difference was more clearly indicated ( P = 0.049). Better sensory recovery predicted high satisfaction scores in patient-reported outcomes ( P = 0.007). Conclusions: We found that subpectoral implant reconstruction and DTI show no statistically significant differences in sensory recovery, and autologous DIEP flap reconstruction results in a better prognosis than prosthesis implant reconstruction. Furthermore, the clarity of the differences increased when the follow-up length was longer than 12 months. Better patient-reported satisfaction was associated with good breast sensibility.